Implementación de la Performance en el Control de Pesos de los Camiones Caterpillar 777F Aplicando Software VIMS. En la Unidad Minera La Arena S.A. - Gamboa Rodríguez, Frank Robert (2017)
Mining unit in the arena, weight control has been carried out from a single source of information, which it provides the operator through daily part of equipment control.This information is not very reliable, since it displays the weight in the ADVISOR, the truck is the operator. For more reliable information it has been implemented weight control through VIMS software. Consisting downloading data mining truck, then processed to obtain information such as weights, truck events, etc.VIMS during application software for weight control, it has been determined and has reached the following results:The tolerable margin of error for the reconciliation between VIMS and GnSys was set at 0.10%. In the month of August, a variation of 0.181% was obtained. In the month of September, a variation of 0.061% was obtained. In the month of October a variation of 0.069%.